Human resource information systems - Kavanagh, Michael J.; Johnson, Richard David
"Human Resource Information Systems, edited by Michael J. Kavanagh and Richard D. Johnson, is a one-of-a-kind book that provides a thorough introduction to the field of Human Resource Information Systems (HRIS) and shows how organizations today can leverage HRIS to make better people decisions and manage talent more effectively. Unlike other texts that overwhelm students with technical information and jargon, this revised Fourth Edition offers a balanced approach in dealing with HR issues and IT/IS issues by drawing from experts in both areas. Numerous examples, best practices, discussion questions, and case studies make this the most student-friendly and current text on the market. New to this edition: a new chapter on social media explores how organizations can use social networks to recruit and select the best candidates, a new HRIS Expert feature spotlights real-world practitioners who share best practices and insights into how chapter concepts affect HR professions and New and expanded coverage of key trends such as information security, privacy, cloud computing, talent management software, and HR analytics is included." -- Amazon